2018
DOI: 10.1038/s41467-018-06995-4
|View full text |Cite
|
Sign up to set email alerts
|

Similarity of introduced plant species to native ones facilitates naturalization, but differences enhance invasion success

Abstract: The search for traits associated with plant invasiveness has yielded contradictory results, in part because most previous studies have failed to recognize that different traits are important at different stages along the introduction–naturalization–invasion continuum. Here we show that across six different habitat types in temperate Central Europe, naturalized non-invasive species are functionally similar to native species occurring in the same habitat type, but invasive species are different as they occupy th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
166
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(183 citation statements)
references
References 61 publications
10
166
2
5
Order By: Relevance
“…Recently, Divíšek et al. () showed that this depends on the invasion stage—naturalized species in central European habitats tend to be similar in their functional traits to native members of the community, while to become invasive, the species need to possess different traits. This idea is supported by the results of a case study on the invasive herb Impatiens glandulifera , which brought new characteristics into the invaded community, such as tall stature, high SLA, and a low leaf dry matter content (LDMC; Helsen et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Divíšek et al. () showed that this depends on the invasion stage—naturalized species in central European habitats tend to be similar in their functional traits to native members of the community, while to become invasive, the species need to possess different traits. This idea is supported by the results of a case study on the invasive herb Impatiens glandulifera , which brought new characteristics into the invaded community, such as tall stature, high SLA, and a low leaf dry matter content (LDMC; Helsen et al.…”
Section: Discussionmentioning
confidence: 99%
“…These traits represent a relatively complete, yet parsimonous, ecological and functional characterization of species (Westoby , Divíšek et al. ). The information on height and life form was obtained from field guides (Armstrong , Pojar and McKinnon , Kershaw et al.…”
Section: Methodsmentioning
confidence: 99%
“…; Divíšek et al . ) and the type of invasion (e.g. wide geographic range vs high local abundance; Catford et al .…”
Section: Introductionmentioning
confidence: 99%
“…Support exists for both the phenotypic divergence (Cleland, ; Gross, Borger, Duncan, & Hulme, ; Knapp & Kühn, ) and convergence (e.g., Drenovsky, Khasanova, & James, ; Lambdon et al., ; Leishman, Thomson, & Cooke, ) hypotheses. Furthermore, these two hypotheses are not necessarily mutually exclusive within a given community: some traits may display convergence and others divergence (e.g., Divíšek et al., ; Tecco et al., ).…”
Section: Introductionmentioning
confidence: 99%